Energy Use for Climate Control of Animal Houses: The State of the Art in Europe. (November 2016) - Costantino, Andrea; Fabrizio, Enrico; Biglia, Alessandro; Cornale, Paolo; Battaglini, Luca
Abstract: Animal rearing is done into houses where heating, cooling, ventilation and lighting are adopted to control the indoor climate, however there are not reference values for the energy performance of such enclosures. In this paper, a first analysis on the energy use for climate control of animal houses that can be found in the technical and scientific literature is done for broilers, hens and pig houses, deriving reference energy use values that may be used for the benchmarking of the performance of these buildings.